Effect of shade and limit feeding on growing cattle during heat stress - DeBord, Zachary L. (Kansas State University, 2023)
Two experiments were conducted concurrently during the summers of 2021 and 2022 to evaluate the effects of shade allocation and diet type on growth performance, animal comfort, water usage, diet digestibility, and ruminal fermentation on growing heifers. In Exp. 1, 852 heifers (initial body weight = 250 ± 28 kg) were purchased from Iowa, Kansas, and Missouri and transported to Kansas State Beef Stocker Unit. Heifers were assigned to one of four treatments: high-energy diet limit-fed at 2.2% body weight (dry matter basis; LIM) or high-roughage diet fed for ad libitum intake (ADLIB) with shade (SH) or without shade (NSH). Pen body weights were measured weekly from day 14 to 84 and individual body weights were measured on days 0, 90, and 97. Pen weights were used to adjust weekly intakes of LIM. Refusals for ADLIB were targeted at 5% of feed consumed the previous day. Following the 90-day feeding period, a gut-fill equilibration diet was fed to all cattle at 2.5% of body weight (dry matter basis) for 7 days to balance for differences in gut-fill between dietary treatments. Dry matter intake was lesser (P < 0.01) for LIM compared with ADLIB. Average daily gain and gain:feed was greater(P ≤ 0.03) for LIM compared with ADLIB. Average daily gain and gain:feed was greater (P < 0.01) for SH compared with NSH. Water usage was less (P < 0.01) for SH heifers compared with NSH and was less (P < 0.01) for LIM compared with ADLIB. Mean panting scores were lower (P < 0.01) for SH compared with NSH and LIM compared with ADLIB. In Exp. 2, 16 heifers (initial body weight = 254 ± 22) were used in digestibility trials to evaluate treatments used in Exp. 1. Apparent total tract digestibility of dry matter and organic matter was greater (P < 0.01) for LIM compared with ADLIB. LIM had a lower (P = 0.03) ruminal pH compared with ADLIB. Liquid passage rate was slower (P < 0.01) for LIM compared with ADLIB. Shade did not affect (P > 0.05) diet digestibility; however, SH had greater (P < 0.01) ruminal pH compared with NSH. In conclusion, limit-fed high-energy diets improved feed efficiency, reduced mean panting score and reduced water consumption compared with diets fed for ad libitum intake. In addition, shade improved growing calf performance, reduced water usage, and improved animal comfort during periods of heat stress. Utilization of limit-fed high-energy diets and the use of shade during periods of heat stress may improve animal comfort, decrease water usage and improve growing calf performance.
Keywords: Growing cattle; Heat stress; Limit feeding; Shade; Water